Respuesta :

Answer:

x = 4/9

C

Step-by-step explanation:

log_2(6x/) - log_2(x^(1/2) = 2         Given

log_2(6x/x^1/2) = 2                         Subtracting logs means division

log_2(6 x^(1 - 1/2)) = 2                     Subtract powers on the x s

log_2(6 x^(1/2) ) = 2                         Take the anti log of both sides

6 x^1/2 = 2^2                                    Combine the right

6 x^1/2 = 4                                        Divide by 6  

x^1/2 = 4/6 = 2/3                               which gives 2/3 now square both sides

x = (2/3)^2                                      

x = 4/9

Answer:

Option c

Step-by-step explanation:

The given logarithmic equation is

[tex]log_{2} (6x)-log_{2}(\sqrt{x})=2[/tex]

[tex]log_{2}[\frac{(6x)}{\sqrt{x}}]=2[/tex] [since log[tex](\frac{a}{b})[/tex]= log a - log b]

[tex]log_{2}[\frac{(6\sqrt{x})\times\sqrt{x}}{\sqrt{x}}]=2[/tex] [since x = [tex](\sqrt{x})(\sqrt{x})[/tex]]

[tex]log_{2}(6\sqrt{x} )=2[/tex]

[tex]6\sqrt{x} =2^2[/tex]  [logₐ b = c then [tex]a^{c}=b[/tex]

[tex]6\sqrt{x} =4[/tex]

[tex]\sqrt{x} =\frac{4}{6}[/tex]

[tex]\sqrt{x} =\frac{2}{3}[/tex]

[tex]x=(\frac{2}{3})^2[/tex]

        = [tex]\frac{4}{9}[/tex]

Option c is the answer.

ACCESS MORE